Responses of Lemongrass (Cymbopogon citratus) Essential Oils Supplementation on in Vitro Rumen Fermentation Parameters in Buffalo - Singh, Ram Kumar; Dey, Avijit; Paul, Shyam Sundar; Singh, Mala; Punia, B.S. (Indian Journal of Animal Nutrition, 2018)
The present study was carried out to investigate the effect of addition of graded dose of lemon grass (Cymbopogon citrates) essential oils (LGO) on in vitro rumen digestibility and fermentation parameters in buffalo. Two separate experiments were conducted with either oats hay or a mixed feed (oats hay: concentratemixture, 60: 40) as substrate in completely randomized design with control (without LGO) and added with LGO @ 10, 20, 40 and 80 Î¼L of LGO/40 mL of buffered rumen fluid. Incubations were carried out in 125 mL serum bottle under anaerobic conditions at 39Â°C for 24 h. Methane concentration (%) in the head space gas reduced(P